Quality of Life in Communities of Latin Countries - Tonon, Graciela (Springer International Publishing : Imprint: Springer, 2017)
This book presents a reconfiguration of the concepts of community in Latin countries as well as the community quality of life and well-being of different groups: children, young people, older adults, migrants. The traditional concept of community has changed together with the way people participate in community spaces. Community nowadays is more than a geographic concentration; it is related to social support, inter-subjectivity, participation, consensus, common beliefs, joint effort aiming at a major objective, and intense and extensive relationships. This volume presents unique experiences about culture, social development, health, water, armed conflicts, the digital media, and sports within communities, written by authors from Latin countries. this volume is a valuable resource for researchers, students and policy makers in quality of life studies.
Keywords: Social sciences.; Ethnology -- Latin America.; Medical research.; Quality of life.; Social service.; elektronické knihy; electronic books